Effect of Levels of Lucerne Straw in Total Mixed Ration on Rumen Fermentation Pattern and Blood Metabolites in Bullocks - Lunagariya, P.M.; Pande , M.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A study was planned to ascertain effect of 50 (TJ, 60 (T2) and 70 (T3) % lucerne straw in total mixed ration (TMR) on rumen fermentation and blood metabolites in Kankrej crossbred bullocks. Two bullocks were assigned in each treatment using 3 x 3 Latin Square design. The rumen and blood metabolites were evaluated on last day of each period. The pH of strained rumen liquor (SRL) was slightly alkaline (7.09-7.16) on account of green forage feeding in morning before TMR. The pH was lowest at 4 hr post-feeding. The total volatile fatty acids (TVFAs) were 75.79-77.67 mEq/ litre and a reverse trend was observed for TVFAs as compared to pH. The values for ammonia, total, soluble, non-protein and protein nitrogen in SRL were 15.07-17.52, 86.92-90.07, 39.90-46.55, 35.88-40.69 and 46.23-53.50 mg/100 ml, respectively. All nitrogen fractions peaked at 2 hr post feeding, except protein nitrogen which peaked at 6 hr, showing maximum activity up to 6 hr post feeding. The values for serum protein, phosphorus and calcium as well as blood haemoglobin were within physiological range. The differences amongst treatments for rumen and blood metabolites were non-significant. The results suggest that lucerne straw can be incorporated up to 70% in TMR of bovines for maintenance without adverse effect on rumen fermentation and blood constituents.